A New Estimator for Shannon Entropy - Alizadeh Noughabi, Hadi; Shafaei Noughabi, Mohammad (Statistics, Optimization & Information Computing, 2025)
In this paper we propose a new estimator of the entropy of a continuous random variable. The estimator is obtained by modifying the estimator proposed by Vasicek (1976). Consistency of the proposed estimator is proved, and comparisons are made with Vasicek’s estimator (1976), Ebrahimi et al.’s estimator (1994) and Correa’s estimator (1995). The results indicate that the proposed estimator has smaller mean squared error than considered alternative estimators. The proposed estimator is applied to a real data set for illustration.